2008
DOI: 10.2298/sarh0810481t
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of streptokinase and alteplase on electrocardiogram and angiogram signs of myocardial reperfusion in ST segment elevation acute myocardial infarction

Abstract: Alteplase with modern adjuvant therapy of ST segment elevation acute myocardial infarction shows the earlier achievement of coronary perfusion as well as better coronary flow compared to streptokinase. There is no statistically significant difference in the frequency of reperfusion arrhythmias, degree of residual stenosis at the"culprit"artery and the frequency of new coronary events in the 6-month-follow-up period after acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…All three studies have also indicated that the choice of fibrinolytic agent is less important for the survival of the patient, i.e. the of primary importance has the time from initial symptoms to treatment (1,5,8,9,10,11,14). .…”
Section: Discussionmentioning
confidence: 99%
“…All three studies have also indicated that the choice of fibrinolytic agent is less important for the survival of the patient, i.e. the of primary importance has the time from initial symptoms to treatment (1,5,8,9,10,11,14). .…”
Section: Discussionmentioning
confidence: 99%
“…The current treatments for myocardial infarction, including the administration of thrombolytic drugs (e.g. streptokinase, urokinase and alteplase) (Tomasevic et al, 2008 ; Minami et al, 2010 ; Sehestedt et al, 2011 ; Lyngbaek et al, 2012 ; Juarez-Herrera and Jerjes-Sanchez, 2013 ; Lippi et al, 2013 ), the implantation of vascular stents (Armstrong, 2006 ; Stefanini and Windecker, 2012 ; Tokushige et al, 2013 ; Zhang et al, 2013 ) and bypass operation (Favaloro, 1969 , 1971 ) mainly concentrated on improving the hemodynamics thus restoring the blood supply to infarcted myocardium. Nonetheless, the efficacy of these conventional therapies was limited as they could hardly compensate for the massive loss of necrotic cardiomyocytes, which account for approximately 25% of total cardiomyocytes during a single episode of infarction (Deutsch et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistency of evidence regarding the role of diabetes in ST resolution after fi brinolytic therapy as a sign of reperfusion may partly originate from applying different criteria for assessing the response to fi brinolytic therapy. Another point to mention is the use of various fi brinolytic agents in studies [15,30] that may differ in therapeutic response or time to accomplish the full reperfusion [19]. Although in our patients, diabetes did not have a signifi cant impact on reperfusion success by using electrocardiographic criteria 90 minutes after treatment with streptokinase, diabetics had higher prevalence of three--vessel coronary disease in subsequent angiographic studies, performed during hospital stay and not as a rescue procedure.…”
Section: Discussionmentioning
confidence: 73%
“…Other predictors of ST resolution are not also consistent in various studies [3,16,17]. On the other hand, including the patients of clinical trials [18] and using different fi brinolytic medications in some of these studies [14] which may have dissimilar therapeutic responses [9,19], complicates the interpretation and application of the results to a single agent in real-life clinical settings. In addition, there are studies that have reported diminishing adverse impact of diabetes on short-term outcomes after myocardial infarction at least in certain subsets of population, which is attributed partly to the better use of therapeutic methods in diabetics [20,21].…”
Section: Introductionmentioning
confidence: 99%